STUDENTS' ACADEMIC SELF-CONCEPT AND THEIR ABILITY IN SOLVING MATHEMATICAL PROBLEMS - Saputro, Marhadi; Fajriah, Fajriah; Fadillah, Syarifah (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
The connection between academic self-concept and mathematics achievement has been widely studied, but the consideration from students’ internal process when solving a mathematical test is surprisingly rare. Students’ mathematical problem-solving ability was evaluated from their ability to solve trigonometry problems, while students’ academic self-concept was obtained from a questionnaire. The result indicated that students’ academic self-concept is linearly connected with their ability to solve mathematical problems. Students with high academic self-concept also possess an excellent ability to solve mathematical test problems and vice versa.